How to start a restaurant and five other food businesses : [your step-by-step guide to success]. - Shaw, Michael Drew ([United States] : Entrepreneur Media, 2003)
Whether your dream is to open a little cafe on the corner of the next hottest spot in town, this easy-to-use audio guide tells you everything you need to know to carve off a healthy slice of this
Narrated by Michael Drew Shaw.
Keywords: Restaurant management; Food service management